2021
DOI: 10.1186/s13041-021-00743-4
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between genetically determined metabolites and human intelligence: a Mendelian randomization study

Abstract: Intelligence predicts important life and health outcomes, but the biological mechanisms underlying differences in intelligence are not yet understood. The use of genetically determined metabotypes (GDMs) to understand the role of genetic and environmental factors, and their interactions, in human complex traits has been recently proposed. However, this strategy has not been applied to human intelligence. Here we implemented a two-sample Mendelian randomization (MR) analysis using GDMs to assess the causal rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Considering that people with chronic pain are often accompanied by anxiety disorders, epiandrosterone sulfate might play a role in neurodevelopment of anxiety disorders. In addition, p-acetamidophenylglucuronide showed robust association with intelligence, and thus it can be used to predict important health outcomes that may affect anxiety disorders [ 15 ]. It is worth mentioning that our results are consistent with above results and emphasize the significance of genetics in the progression of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that people with chronic pain are often accompanied by anxiety disorders, epiandrosterone sulfate might play a role in neurodevelopment of anxiety disorders. In addition, p-acetamidophenylglucuronide showed robust association with intelligence, and thus it can be used to predict important health outcomes that may affect anxiety disorders [ 15 ]. It is worth mentioning that our results are consistent with above results and emphasize the significance of genetics in the progression of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that metabolites are the final products or the intermediate of metabolism that can play important in human. The database of genotype dependent metabolic phenotypes (also known as genetically determined metabolites (GDMs)) has recently been established using a GWAS involving non-targeted metabolomics [ 15 , 16 ]. The developed GDMs can promote insight of the underlying relationship of human serum metabolites and associative genetic variants in the biological mechanisms of mental disorders by providing functional intermediates [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified the SNPs affecting Hcy, not directly MetS, suggesting that the associated genetic variants might provide information on the biological mechanisms of MetS. Hcy might be a functional intermediate to understand the biological process through which genetics affect MetS [ 45 , 46 ]. The strength of the causal relationship between modifiable exposure and risk of disease identified by MR can also help improve the drug target identification or drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Because re-referencing techniques can introduce their own physiological signals (Bigdely-Shamlo et al, 2015;Yang et al, 2021), these can also interact with other preprocessing steps to materially alter the information contained in measurements involving them. To point out an obvious example, an average reference will perform relatively poorly compared to a linked mastoids reference when the subject is the lateralization of brain activity, but for global information, it ought to afford superior performance through yielding higher sensitivity.…”
Section: Laskermentioning
confidence: 99%